Biodegradation of Sewage Wastewater Using Autochthonous Bacteria - Purnima Dhall; Rita Kumar; Anil Kumar (The Scientific World Journal)
The performance of isolated designed consortia comprising Bacillus pumilus, Brevibacterium sp, and Pseudomonas aeruginosa for the treatment of sewage wastewater in terms of reduction in COD (chemical oxygen demand), BOD (biochemical oxygen demand) MLSS (mixed liquor suspended solids), and TSS (total suspended solids) was studied. Different parameters were optimized (inoculum size, agitation, and temperature) to achieve effective results in less period of time. The results obtained indicated that consortium in the ratio of 1 : 2 (effluent : biomass) at 200 rpm, 35°C is capable of effectively reducing the pollutional load of the sewage wastewaters, in terms of COD, BOD, TSS, and MLSS within the desired discharge limits, that is, 32 mg/L, 8 mg/L, 162 mg/L, and 190 mg/L. The use of such specific consortia can overcome the inefficiencies of the conventional biological treatment facilities currently operational in sewage treatment plants.